Ancillary Services of a Grid-Connected Inverter with Overcurrent Protection Capability under Voltage Sag - Sepannur Bandri; Zuriman Anthony; Rafika Andari; Fauzan Ismail (Jurnal Teknik Elektro, 2023)
The Distributed Generator of a Photovoltaic System (DGPVS) is an essential factor for future power plant generation, and it can be created by connecting multiple small power plant generators in a microgrid system. This paper focuses on the overcurrent protection of a three-phase grid-connected inverter (3P-GCI) under voltage sag conditions in sustaining connection loss between the 3P-GCI and the primary grid, which involves voltage instability. The ancillary service shows more advantage in overcurrent protection during voltage sags, which limits the generated current under sag duration. Its service can protect the inverter and avoid more disturbances to the primary grid because the 3P-GCI remains connected. Proposed LVRT strategy with limit current feature play the role to protect 3P-GCI under voltage sag. In the normal grid, the 3P-GCI can inject 302W of active power with a power factor (PF) equal to one. 1.4% of VTHD and 4.3% of ITHD shows the performance of the proposed system. Meanwhile, the 3P-GCI injects 239VAr reactive power and reduces injected active power to 135W which is essential to remain connected to the primary grid during voltage sags and limit the generated current. The validation results show that this prototype successfully compensates for the grid voltage drops by injecting 239Var of reactive power and limiting its generated current to 1.592A.